Bodzia : A Late Viking-Age Elite Cemetery in Central Poland - Buko, Andrzej (East Central and Eastern Europe in the Middle Ages, 450-1450 Ser, 2014)
Table of Contents -- List of Illustrations -- List of Tables -- List of Contributors -- Looking Towards Bodzia: An Introduction -- Part 1 The Area of the Middle and Lower Vistula River Valley between the 10th-11th Centuries: Archaeology and History -- Chapter 1 The Archaeological Context of the Bodzia Cemetery and the Trade Route along the Middle and the Lower Vistula during the Middle and Late Viking Period -- Chapter 2 The Historical Context of the Discoveries at Bodzia -- Part 2 The Bodzia Cemetery: Site Location, Environmental Data, Graves and their Contents -- Chapter 3 Bodzia: Site Location and History of Research -- Chapter 4 The Effect of Depositional and Post-Depositional Processes on the Preservation of Skeletal Remains in the Bodzia Cemetery -- Chapter 5 The Inventory of the Burials and their Contents -- Appendix: Wood and Plant Macro-Remains Analysis -- Chapter 6 Analysis of the Skeletal Population from the Cemetery of Bodzia -- Part 3 Grave Goods and their Context -- Chapter 7 Overview of the Finds from the Bodzia Cemetery -- Chapter 8 Merchants' Implements (The Folding Balance) -- Chapter 9 Weapons -- Appendix: Metallographic Analyses of Selected Finds from a Young Warrior's Grave (E864/I) -- Chapter 10 Status and Magic. Ornaments Used by the Bodzia Elites -- Chapter 11 Glass Beads -- Chapter 12 Iron Artifacts -- Chapter 13 Costume Elements of Leather -- Chapter 14 Ceramic and Wooden Containers -- Chapter 15 Objects Made of Antler and Stone -- Chapter 16 The Obol of the Dead -- Part 4 Funeral Rites -- Chapter 17 Description of the Cemetery, Organization of the Burial Space, the Burial Rites in the Light of the Cultural and Historical Determinants -- Chapter 18 Tentative Reconstruction of Coffins -- Chapter 19 Symbolic Aspects of the Remains of Wood from the Cemetery -- Part 5 Chronology of the Cemetery.